Law and Violence: a study on Walter Benjamin's Thinking - Perius, Oneide (Argumentum, 2020)
Abstract: The article proposes an analysis of the conditions for the possibility of criticizing violence in contemporary societies. To achieve this objective, the philosophy of the young Walter Benjamin is used. Two aspects will be especially highlighted. The first refers to the need to go beyond the criticisms made by pacifists, towards a critique of the social and legal structure. The second aspect to be highlighted is that Gewalt – a Benjaminian term that signifies violence and power simultaneously – is never fully absorbed into a given order. The conditions for the possibility of the destitution of the existing order are, therefore, contained in the dialectical dynamics of this concept.Keywords: Violence. Power. Law. Critique. Walter Benjamin.